Perilaku Konsumsi Muslim: Pengaruh Label Halal, Harga, dan Kualitas Produk di Kabupaten Takalar: Muslim Consumer Behavior: The Influence of Halal Label, Price, and Product Quality in Takalar Regency - huda, Nadial; Kasim, Muhammad Najib; Wahyuni, Sri (Journal of Islamic Economics and Philanthropy, 2025)
This research is motivated by the large number of packaged foods circulating among the Muslim community. The purpose of this research is to examines the Influence of Halal Labels, Prices, and Product Quality on Islamic Consumption Behavior on Packaged Food in Takalar Regency. This type of research is quantitative obtained from the questionnaire. The sampling technique uses simple Random Sampling. The number of samples used is 100 respondents obtained using the slovin formula. The data analysis technique used is multiple linear regression using SPSS 24. The results of the Halal Label study do not have a significant effect on Islamic consumption behavior on packaged food in Takalar Regency because the t-count value is 0.526 <t table of 1.984. Price has a positive and significant effect on Islamic consumption behavior on packaged food in Takalar Regency because the t-count value is 2.153> t table of 1.984. And Product Quality has a positive and significant influence on Islamic consumption behavior on packaged food in Takalar Regency because the t-count value is 5.932 > t-table of 1.984.